2013
DOI: 10.4236/ojvm.2013.32031
|View full text |Cite
|
Sign up to set email alerts
|

Association between Presence of Urovirulence Factors, Phylogenetic Class, and Antimicrobial Resistance Patterns in 159 Uropathogenic <i>Escherichia coli</i> Samples Isolated from Dogs

Abstract: The purpose of this study was to examine four urovirulence factors (UVFs) and their phylogenetic classes and compare their levels of resistance to antimicrobial drug classes in 159 canine uropathogenic E. coli (UPEC) isolates submitted to the Clinical bacteriology and Mycology Laboratory of The University of Tennessee Veterinary Medical Center in 2007. Multiplex polymerase chain reaction was used to detect the following UVFs: cytotoxic necrotizing factor (cnf), hemolysin (hly), S-fimbrial adhesion gene (sfa), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…al. (39) reported that they detected 25% cnf1 gene in 159 E. coli isolates from canine patients in 2007. This result showed that cytotoxic necrotizing factor was common and important virulence factor in uropathogenic E. coli and prognosis of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. (39) reported that they detected 25% cnf1 gene in 159 E. coli isolates from canine patients in 2007. This result showed that cytotoxic necrotizing factor was common and important virulence factor in uropathogenic E. coli and prognosis of infection.…”
Section: Discussionmentioning
confidence: 99%
“…UPEC causes various diseases as opportunistic pathogens in humans and animals, especially in cats and dogs. These bacteria can also cause vaginitis, pyometra especially in femeale dogs rather than female cats (2,4,6) cystitis and pyelonephritis (4,39). E. coli is the most isolated (62-90%) bacteria in pyometra.…”
Section: Introductionmentioning
confidence: 99%